Proposing the Cognitive Space Theory: A Map to Explore the Mind - Goulet-Pelletier, Jean-Christophe (Université d'Ottawa / University of Ottawa, 2023)
This thesis attempts to answer a central question in the field of creativity: what creativity looks like in various domains of activities ? Finding a satisfying answer to this question involves answering what 'creativity' is. Therefore, the first chapter is dedicated to establishing a shared understanding of the term creativity. Following this, determining what creativity looks like in various domains is answered in that same chapter with a new theory of cognition, called the Cognitive Space Theory. This theory organizes the content of domains according to ten fundamental cognitive spaces. These cognitive spaces cover a broad range of human creative expressions. In the second chapter, a questionnaire based on the theory is developed and validated. This questionnaire assesses the exploration and mastery of the ten cognitive spaces postulated in the theory. The results of two studies are reported to demonstrate the psychometric properties of the questionnaire. The third chapter uses the latter questionnaire to predict the creative activities and creative achievements of university students in eight different domains ranging from sport to science. Finally, the fourth chapter discusses the implications of the theory applied to education. The chapter concludes with future avenues of research in neuroscience, cognition, and artificial intelligence.
Keywords: Creativity; Divergent Thinking